Wilhelm Hasselbach: a personal tribute - Rüegg, Johann Caspar (Journal of muscle research and cell motility, 2016)
Wilhelm Hasselbach (1921-2015) is best known for his major contribution to the discovery and molecular elucidation of an ATP-driven active ion transport across a biological membrane. He had discovered SERCA, the calcium pump of the sarcoplasmic reticulum (Hasselbach and Makinose in Biochem Z 333:518-528, 1961; Biochem Z 339:94-111, 1963).
Gesehen am 06.05.2020